Chemical constituents and cytotoxic properties of Goniothelamus Macrophyllus / Hamidah Sahibul Anwar - Sahibul Anwar, Hamidah (2008)
The roots of Goniothalamus macrophyllus (Annonaceae), commonly known as "akar gajah beranak" by Malaysian is traditionally consumed by women after child birth.